(untitled) (Physical Education, Health and Social Sciences, 2025)
The prevalence of addictive behaviors among adults with substance use disorders (SUDs) is a critical area of study due to its implications for intervention and treatment. This study investigated the prevalence of various addictive behaviors, including gambling, drug use, social networking addiction, and sexual addiction, among adults with SUD. The independent variables include demographic information and scores on scales measuring addictive behaviors, while the dependent variable is the presence and severity of addictive behaviors. A cross-sectional research method was used, with a sample size of at least 350 participants. The study encompassed a diverse representation of individuals with addictive behaviors, utilizing a sample of individuals aged 18 to 65 years, a stratified random sampling strategy based on the type of substance that was used. The findings revealed that gambling symptoms were significantly correlated with substance use (r = .16, p < .01), social networking addiction (r = .02, p < .01), and sexual addiction (r = .06, p < .01). Furthermore, sexual addiction showed significant positive correlations with both substance use (r = .42, p < .01) and social networking addiction (r = .22, p < .01). Gender comparisons showed that males reported significantly higher mean scores than females. The anticipated findings of this study illuminated the co-occurrence of addictive behaviors in individuals with SUDs, underscoring the necessity for integrated treatment and intervention strategies. Gaining insight into the prevalence and patterns of these behaviors within this population holds considerable implications for developing tailored interventions and support services.